Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve by substitution
X+3y=1 and -3x-3y=-15


Sagot :

[tex]x+3y=1\\ -3x-3y=-15\\ add\quad the\quad equ.\\ (x+3y)+(-3x-3y)=1-15\\ x-3x+3y-3y=-14\\ -2x=-14\\ x=\frac { -14 }{ -2 } \\ x=7\\ Let's\quad rewrite\quad the\quad equ.\\ 7+3y=1\\ 3y=1-7\\ 3y=-6\\ y=\frac { -6 }{ 3 } \\ y=-2[/tex]